HMI dan Budaya Populer - Faradina (STAI DDI Kota Makassar, 2022)
This journal discusses the correlation and transformation of the Human Rights Organization and National Culture that occurs in the scope of the organization and in Indonesia, and makes it an intellectual benchmark in understanding cultural values ​​in the current era. When talking about popular culture means inseparable from the actions of society. Society is a group of people who live together in an area and form a system, both semi-open and semi-closed, where the interactions that occur in it are between individuals in the group. Popular culture represents the way of life that the average person enjoys and has. Culture is said to be popular if it always experiences artistic development, it is attractive and commercial in nature and can be used to express and understand the wider community. In the process of popular culture, the media also plays a role as the dissemination of information and entertainment technology, as well as an institution that creates and controls the commodity market in a social environment. The purpose of this research is also to be used as a reference for students as HMI cadres when discussing the insight of the archipelago in national culture and popular culture in the Unitary State of the Republic of Indonesia.